중국 미용전공자들의 피부미용 국가자격증 도입에 대한 인식 연구 - 루야오; Lu-yao; 전선영; Sun-young Jeon; 신규옥; Kyu-ok Shin (한국미용학회지, 2023)
The purpose of this study was to introduce a national technical qualification certificate for esthetician in China, where interest and demand for ‘Beauty’ is rapidly increasing based on recent economic development. The beauty industry in China is currently positioned as a promising occupation with high added value. Therefore the national technical qualification certificate for esthetician system that is being implemented in Korea was investigated, And this study conducted a survey on the introduction of national technical qualification certificate for beauty majors in China from February 12 to February 18, 2023, and conducted a self-written survey using WeChat and the Wenjunxing program, which are available for online surveys in China. The final 302 of the survey results were used as analysis data and analyzed using the SPSS WIN 25.0 program., there are limitations in generalizing the results to all of China. In the future, if an extensive survey is conducted targeting beauty majors in more regions, it is considered to be helpful in introducing national technical qualification certificate for esthetician in China.